Pengaruh Metode Resitasi dalam Model Pembelajaran Kooperatif untuk Meningkatkan Hasil Belajar Materi Kalor dan Perpindahannya - Lian Kristina Sidani; Amiruddin Hatibe; I Wayan Darmadi (Universitas Tadulako, 2021)
The purpose of this study was to determine whether there is an effect of the recitation method in the cooperative learning model to improve the learning outcomes of heat and its transfer. This type of research was quasi-experimental. The sampling technique was purposive sampling. The samples of this research were students of class VII A and VII B of SMP Negeri 3 Bulagi. Class VII A is the experimental group and class VIIB is the control group. The learning outcome test instrument was a multiple-choice test. Based on the results of data processing, the N-gain value in the experimental group was obtained at 45.97%, which was in the medium category. Then for the control group, the N-gain value was obtained at 33.43%, which was also in the medium category. These results indicate that the learning outcomes of physics in the experimental group are higher than those in the control group. The results of statistical calculations from the average difference test using t-test (two-tailed) obtained tcount > ttable (tcount = 4.22 and ttable = 2.02) at a significance level of 5% and dk = 45, thus H0 is rejected and H1 is accepted. So, it can be concluded that there is an effect of the recitation method in the cooperative learning model to improve the learning outcomes of heat and its transfer.